Direct-to-Consumer Drug Advertisements Can Paradoxically Increase Intentions to Adopt Lifestyle Changes - Mathur, Maya B.; Gould, Michael; Khazeni, Nayer (Frontiers in Psychology, 2016)
Background: Direct-to-consumer (DTC) prescription drug advertisements are thought to induce “boomerang effects,” meaning they reduce the perceived effectiveness of the alternative option: non-pharmaceutical treatment via lifestyle change. Past research has observed such effects using artificially created, text-only advertisements that may not adequate capture the complex, conflicting portrayal of lifestyle change in real television advertisements. Research in other risk domains has found that individual “problem status” often moderates boomerang effects, such that subjects who currently engage in the risky behavior exhibit the strongest boomerang effects. Objectives: We aimed to assess whether priming with real direct-to-consumer (DTC) television advertisements elicited boomerang effects on perceptions of lifestyle change and whether these effects, if present, were moderated by individual problem status. Methods: We assembled a sample of real, previously aired DTC television advertisements in order to naturalistically capture the portrayal of lifestyle change in real advertisements. We randomized 819 adults in the United States recruited via Amazon Mechanical Turk to view or not view an advertisement for a prescription drug. We further randomized subjects to judge either lifestyle change or drugs on three measures: general effectiveness, disease severity for a hypothetical patient, and personal intention to use the intervention if diagnosed with the target health condition. Results: Advertisement exposure induced a statistically significant, but weak, boomerang effect on general effectiveness (p = 0.01, partial R2 = 0.007) and did not affect disease severity score (p = 0.32, partial R2 = 0.0009). Advertisement exposure elicited a reverse boomerang effect of similar effect size on personal intentions, such that advertisement-exposed subjects reported comparatively higher intentions to use lifestyle change relative to drugs (p = 0.006, partial R2 = 0.008). Individual problem status did not significantly moderate these effects. Conclusions: In contrast to previous literature finding large boomerang effects using artificial advertisement stimuli, real television advertisements elicited only a weak boomerang effect on perceived effectiveness and elicited an unexpected reverse boomerang effect on personal intentions to use lifestyle change versus drugs. These findings may reflect real advertisements’ induction of descriptive norms and self-efficacy; future research could address such possibilities by systematically manipulating advertisement content.